RV Pacing Percentage. (25th November 2020) - Cha, Y.M; Metzl, M.D; Canby, R.C; Fruechte, E.M; Duggal, M; Exner, D.V; Chung, E.S; Singh, J.P; O'Donnell, D; Zimmerman, P; Landman, S; Lexcen, D.R; et al.
Abstract: Introduction: Chronic right ventricular pacing (RVP) has been associated with dyssynchrony, leading to increased mortality. However, there have been discrepancies in previous reports in the effect of RVP levels. Objective: To sub-stratify mortality risk by age for different RVP level groups within a large real-world ICD cohort. Methods: Optum® de-identified electronic health records were linked to the Medtronic Carelink data to identify dual chamber ICD recipients (2007–2017). RVP level was based on median daily pacing during the first 90 days post-implant and categorized either into groups with a cutoff of 40%, or with groups of 0–9%, 10–19%, 20–29%, 30–39%, 40–49%, and 50–100%. The endpoint was death more than 90 days post-implant. Kaplan-Meier survival curves, log-rank tests, and Cox regression were used to analyze the relationship between RVP and risk of death. Results: Among 14, 832 ICD patients (median age 67; 74.0% male), there were 2, 602 deaths within 10 years after implant. In unadjusted comparisons, high RVP (>40%) increased the risk of death relative to low RVP (≤40%) (p<0.001). This effect remained significant in older cohort (≥67 years old at implant) (p<0.001), but not in younger cohort (<67 years old) (p=0.955) (Figure). After controlling for age, gender, pacing mode, MI, SCA, HF hospitalization, diabetes, and renal dysfunction, similar or increased risk was associated with higher pacing groups relative to the 0–9% pacing group in the older cohort, but not in the younger cohort. Conclusions: Our data from a large contemporaneous real-world source suggests that older age or characteristics associated with age make patients more sensitive to chronic RVP effects. These results help reconcile differences observed in prior studies. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Medtronic, Inc.